MEMBANGUN SISTEM INFORMASI WEBSITE SEKOLAH DENGAN MENGGUNAKAN GOOGLE SITES - La Ode Muhammad Ramsy Sangkalibu; Hendra Nelva Saputra (Jurnal Isema : Islamic Educational Management, 2022)
Website is an internet media facility that serves to display, introduce and even function as a medium for finding information that is needed. School institutions, especially those that still really need interaction and socialization so that the school can be better known to the wider community and the students themselves. This study aims to design a school website for SMP Negeri 3 Tongkuno so that it can be used as a medium of information to students, teachers or the general public. The method used in this research is the waterfall development method. The development stage in this research begins with analyzing needs, designing, creating a school website, then applying and testing its effectiveness. Based on the results of the black box testing that has been carried out, it shows that the functional website of SMP Negeri 3 Tongkuno as a medium of information, is free from syntax errors and functions as it should. The results of these tests indicate that each menu contained on the school's website functions properly or in other words according to what is expected. Therefore, it can be concluded that the school website information system using google sites at SMP Negeri 3 Tongkuno is feasible to use.